2007
DOI: 10.1007/s00438-007-0247-8
|View full text |Cite
|
Sign up to set email alerts
|

PpRab1, a Rab GTPase from maritime pine is differentially expressed during embryogenesis

Abstract: Rab-related small GTP-binding proteins are known to be involved in the regulation of the vesicular transport system in eukaryotic cells. We report the characterization of a previously isolated full-length cDNA PpRab1 from Pinus pinaster. Amino acid sequence analysis revealed the presence of G1-G5 conserved domains of the GTPase Ras superfamily and a double cysteine motif in the C-terminal, characteristic of Rab proteins. The PpRab1 protein shows high sequence similarity to several Rab1 GTP-binding proteins in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Rab2 is also involved in the maturation of vesicular tubular clusters (VTCs), which are microtubule-associated intermediates in transport between the ER and Golgi apparatus [182]. AtRabB1C could be involved in retrograde or anterograde transport between the ER and Golgi, it has been localized in the ER and Golgi apparatus [183], and shown to have a role in early embryogenesis in plants [184].…”
Section: Discussionmentioning
confidence: 99%
“…Rab2 is also involved in the maturation of vesicular tubular clusters (VTCs), which are microtubule-associated intermediates in transport between the ER and Golgi apparatus [182]. AtRabB1C could be involved in retrograde or anterograde transport between the ER and Golgi, it has been localized in the ER and Golgi apparatus [183], and shown to have a role in early embryogenesis in plants [184].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been evidenced that Rab GTPases expression is modulated in response to variations in levels of phytohormones such as ethylene (Moshkov et al, 2003) and abscisic acid during plant development and germinating seedlings (Cui et al, 2013;Nishimura, 2004). In maritime pine embryogenesis, RAB GTPases were expressed in early stages of embryo development; the transcript was detected in early developmental stages of zygotic embryogenesis and the amount of transcript was progressively reduced in later stages (Gonçalves et al, 2007;Tzafrir et al, 2002).…”
Section: Response To Stimulusmentioning
confidence: 99%
“…This and the accumulation of an endoglycosidase H-sensitive population of the Golgitargeted GFP confirmed that trafficking from ER to the Golgi was inhibited in cells compromised in their RAB1-regulated trafficking activity as a result of DN RAB1b overexpression. Developmentally, a recent study in maritime pine (Pinus pinaster) revealed high levels of expression of a RAB1, PpRAB1, in early zygotic development followed by decline as embryos matured, suggesting a role for this small GTPase in early embryogenesis (Goncalves et al, 2007).…”
Section: Rab1/rabd and Rab2/rabbmentioning
confidence: 99%